Case Study : Ngeebok Carwash Kemaman / Nur Umairah Tumiran - Tumiran, Nur Umairah (2020)
‘Ngeebok CarWash Kemaman’ was founded by Mr. Mohd Azlan bin Walik in Kemaman, Terengganu. The initial idea of opening this car wash was when he constantly commuting from work and seeing a site in a relatively rural area that was strategic enough to open a business. Then, he came up with the idea of opening a car wash since there was no business there. The company is a sole proprietorship business which he and only several staff members carry on. The business was set up on April 12, 2019